(untitled) - Mather, Paul M (Chichester, 1999)
Remotely-sensed images of the Earth’s surface provide information about the geographical distribution and properties of natural and cultural features. Computer processing takes place after the images have been collected, and depends on their physical properties and the applications for which they will be used. Computer Processing of Remotely-Sensed Images is the third edition of this highly regarded textbook
Keywords: Remote sensing; Data processing